Indeterminacy and the Discourse of Inevitability in International Technology Management - Leonardi, Paul M. (Academy of Management Review, 2008)
I consider what effect technologically deterministic rhetoric might have on the process of technology implementation. I argue that deterministic discourse creates an ideological orientation toward technological change—a Discourse of inevitability—which makes the fundamentally indeterminate relationship between technology and culture appear determinate. The implications of the paper concern the need for researchers to take into account how institutionalized images of technology can be used discursively to create outcomes in multinational corporations and how such discourse can promote the interests of powerful actors while marginalizing others.